Analysis of the Drama 'Orang-Orang Setia' by Iswadi Pratama as the Initial Work of an Actor - Syahputra, Andi; Susandro, Susandro; Sari, Dian Permata (Creativity And Research Theatre Journal, 2023)
The presentation of Rahman's character in Iswadi Pratama's drama Orang Setia uses Stanislavsy's acting method which he calls the system. Stanislavsky's system is an acting method created to understand characters scientifically so that they can be presented by actors on stage. In Stanislavsky's acting method, there are three parts that he calls the "triad" of musicians, namely the first creative work of the actor centered on the mind (brain), the second creative work of the actor with his emotions (heart), and the third work of the actor with his body (action). The triad becomes the center of the presenter's creative work to realize the character of Rahman in the drama Orang Setia by Iswadi Pratama so that the acting presented can give a natural impression, not contrived. More than that, the behavior presented can be measured as in everyday life, especially by ordinary audiences.